2023
DOI: 10.3389/fpls.2023.1149114
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of soybean drought response by mepiquat chloride pretreatment

Abstract: IntroductionSoybean is the world’s most important cultivated crop, and drought can affect their growth and, eventually, yields. Foliar application of mepiquat chloride (MC) can potentially alleviate the damage caused by drought stress in plants; however, the mechanism of MC regulation of soybean drought response has not been studied.MethodsThis study investigated the mechanism of soybean drought response regulation by mepiquat chloride in two varieties of soybean, sensitive Heinong 65 (HN65) and drought-tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…3 ). In another study, we found that MC promoted the accumulation of some amino acids and flavonoids to withstand drought at the metabolic level [ 32 ]. Lee et al [ 33 ] reported that MC pretreatment before drought promoted drought resistance in cotton during the peak water demand period and reduced the risk of drought.…”
Section: Discussionmentioning
confidence: 99%
“…3 ). In another study, we found that MC promoted the accumulation of some amino acids and flavonoids to withstand drought at the metabolic level [ 32 ]. Lee et al [ 33 ] reported that MC pretreatment before drought promoted drought resistance in cotton during the peak water demand period and reduced the risk of drought.…”
Section: Discussionmentioning
confidence: 99%
“…Some plant growth regulators, such as mepiquat chloride, are commonly used to regulate cotton plant type, but can also increase soluble protein content and antioxidant enzyme activity ( Zhang et al., 2022d ). It can also promote the accumulation of flavonoids in soybeans to enhance drought resistance ( Figure 3 ) ( Wang et al., 2023a ). There are also some other regulators, such as 24-epibrassinolide·triacontanol, indolebutyric acid·triacontanol, indolebutyric acid·S-abscisic acid, kinetin and triacontanol·6-benzylaminopurine, which have similar ways to improve drought resistance ( Lv et al., 2023 ).…”
Section: Methods To Improve Drought Tolerancementioning
confidence: 99%
“…MC regulates a wide range of biological activities in various crops [ 58 ]. In response to abiotic stresses, MC decreased vegetative growth while increasing crop yield in soybean and cotton under drought stress [ 40 , 59 ]. Exogenous MC treatment in cotton can enhance fiber growth and production while reducing the leaf area, stem elongation, and plant height [ 60 ].…”
Section: Biosynthesis Signaling and Transduction Pathways Of MC And Mtmentioning
confidence: 99%
“…MC application slowing GA activity involved in cell elongation restricts signaling and transduction pathways activation, hinders vegetative development, and alters GA homeostasis by activating site-specific genes, reducing plant height ([ 55 ], Figure 1 ). MC inhibited soybean growth by decreasing the concentrations of GA, brassinolide, zeatin, and other plant hormones and signaling pathway-related genes [ 40 ]. MC affects the signaling of various hormones [ 16 ].…”
Section: Biosynthesis Signaling and Transduction Pathways Of MC And Mtmentioning
confidence: 99%